Freshwater Megafauna: Flagships for Freshwater Biodiversity under Threat. (20th September 2017) - Carrizo, Savrina F.; Jähnig, Sonja C.; Bremerich, Vanessa; Freyhof, Jörg; Harrison, Ian; He, Fengzhi; Langhans, Simone D.; Tockner, Klement; Zarfl, Christiane; Darwall, William
Abstract: Freshwater biodiversity is highly threatened and is decreasing more rapidly than its terrestrial or marine counterparts; however, freshwaters receive less attention and conservation investment than other ecosystems do. The diverse group of freshwater megafauna, including iconic species such as sturgeons, river dolphins, and turtles, could, if promoted, provide a valuable tool to raise awareness and funding for conservation. We found that freshwater megafauna inhabit every continent except Antarctica, with South America, Central Africa, and South and Southeast Asia being particularly species rich. Freshwater megafauna co-occur with up to 93% of mapped overall freshwater biodiversity. Fifty-eight percent of the 132 megafauna species included in the study are threatened, with 84% of their collective range falling outside of protected areas. Of all threatened freshwater species, 83% are found within the megafauna range, revealing the megafauna's capacity as flagship and umbrella species for fostering freshwater conservation.